Profit efficiency and liquidity risk : lessons from Malaysia - Nur Alya Afiqah Mohamed Khairuddin; Aisyah Abdul Rahman; Syajarul Imna Mohd Amin (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigates the relationship between profit efficiency and liquidity risk for Malaysian banks involving 16 Islamic and 26 conventional banks from 1995 to 2015. Profit efficiency scores are estimated using the Stochastic Frontier Approach (SFA), while liquidity risks are measured by the Basel III liquidity risk requirements: liquidity coverage ratio (LCR) and net stable funding ratio (NSFR). The results show that the profit efficiency of both Islamic and conventional banks is positively related to liquidity risk in the short run. However, the negative effect of profit efficiency on liquidity risk is only present in Islamic banks in the long run. The findings highlight two important notions: (1) The effect of profit efficiency on liquidity risk is sensitive to the term of liquidity; and (2) profit efficiency requires time to reduce liquidity risk in banking.JEL Classification: G01, G12, G21.